Heads up-Four Giraffa species have distinct cranial morphology - Kargopoulos, Nikolaos; Marugán-Lobón, Jesús; Chinsamy, Anusuya; Agwanda, Bernard R; Brown, Michael Butler; Fennessy, Stephanie; Ferguson, Sara; Hoffman, Rigardt; Lala, Fredrick; Muneza, Arthur; Mwebi, Ogeto; Otiende, Moses; et al. (PloS one, 2024)
Giraffe (Giraffa spp.) are among the most unique extant mammals in terms of anatomy, phylogeny, and ecology. However, aspects of their evolution, ontogeny, and taxonomy are unresolved, retaining lingering questions that are pivotal for their conservation. We assembled the largest known dataset of Giraffa skulls (n = 515) to investigate patterns of cranial variability using 3D geometric morphometrics. The results show distinct sexual dimorphism and divergent ontogenetic trajectories of skull shape for the north clade (G. camelopardalis antiquorum, G. c. camelopardalis, G. c. peralta, and G. reticulata) and the south clade (G. giraffa angolensis, G. g. giraffa, G. tippelskirchi tippelskirchi, and G. t. thornicrofti) which was further supported statistically. Discriminant functions found statistically significant cranial shape differences between all four Giraffa species, and in some cases also between subspecies of the same species. Our 3D morphometric analysis shows that the four genetically distinct Giraffa spp. also have distinct cranial morphologies, largely addressable to features of display (ossicones). Our results highlight the importance of focusing future giraffe conservation efforts on each taxon to maintain their unique characteristics and biodiversity in the wild.
Keywords: Skull; Species Specificity; pohlavní dimorfismus; Female; Biological Evolution; Animals; lebka; ženské pohlaví; mužské pohlaví; druhová specificita; Male; Phylogeny; žirafy; zvířata; fylogeneze; biologická evoluce; Sex Characteristics; Giraffes